Malaysia’s Case study of Forest Resources Management and Development (Journal of Governance and Development (JGD), 2018)
Forest resources development is one of the terms in forest development planning and forest development resource. Similarly, it always involves the effects and impact toward the surroundings, especially regarding human life. This study shall deï¬ne environmental forest resources development and the forest management in the Malaysian context for assisting the nation in achieving the target of maintaining sustainable development for the country. As a rapidly developing country, Malaysia needs resources, especially environmental resources. Development of environmental resources has led to rapid enhancements of its economy manifesting as the positive changes in the cultural landscape of the country. This paper will discuss the review of environmental management and environmental resources in Malaysia. Nevertheless, forest is one of the part of environmental component highlighted in this paper. Therefore, this paper reveals the important things of knowledge associated with forest and the forest management in Malaysia.